Review of lists and recommendations for interchangeability of medicines across selected European countries - Pejčić, Zorica; Topić Vučenović, Valentina; Miljković, Branislava; Vučićević, Katarina (Archives of Pharmacy, 2024)
Generic substitution has been introduced in the healthcare systems of many countries to reduce the costs and ensure the continuity of drug market supply. Common and country-specific strategies on this topic have been presented for several European countries, as well as for the Republic of Serbia. The factors that need to be considered when assessing the interchangeability of medicines may be related to the medicine or the individual patient. Particular caution is required with narrow therapeutic index drugs, drugs with non-linear pharmacokinetics, antiepileptic drugs, medicines with prolonged release formulations, medicines administered in a specific way or with a medical device. Factors such as the different appearance of the medicines, excipients, packaging, indications, but also the patient’s condition, age, concomitant diseases, pregnancy, hand function, vision, ability to swallow, and the patient’s attitude towards the alternative medicines should also be taken into account. When substituting two generic medicines, it should be noted that those medicines may not be bioequivalent, since bioequivalence is confirmed between a generic medicine and a reference (usually original) medicine, and thus pose an additional risk to the patient’s safety. Some countries have opted to form lists of interchangeable medicines and/or detailed guidelines regarding interchangeability to assist healthcare professionals in making decisions on drug substitution.